Intertextual, action-orientated, political and occasioned constructions of Zimbabwe as a country in crisis. (January 2021) - Hall, Laura
The notion that textual, verbal and visual representations of places are more or less accurate depictions of reality has been challenged by cultural geographers and discursive psychologists who regard language as constitutive rather than reflective. This paper builds on this work by demonstrating that constructions of Zimbabwe produced by UK residents from Zimbabwe during life history interviews in 2011 appropriated other representations; were action-orientated; had political consequences; and were orientated to the interactional context in which they were produced. More specifically, I show that the interviewees challenged the 'narrative of the nation' promoted by the ruling party and their supporters by producing intertextual constructions of Zimbabwe as a country in crisis; attributed blame for the crisis; and accounted for their presence in the UK.